(untitled) (Economic and Political Thought, 2018)
In the year 1989 Poland began to reform its political and economic system. In parallel it started to implement the processes of Europeanization. Rapprochement with the western structures became the main objective of the Polish foreign policy. The ultimate goal was the full membership of the NATO and European Union. The Weimar Triangle was established in August 1991, it was one of the tools which should help Poland in achieving this objective. Regular meetings of Ministers of Foreign Affairs and other Polish, German and French politicians took place within this area of cooperation. In the article I analyse the actual impact of this form of cooperation on the processes of European integration in the years 1991–2004.